Penerapan Biblical Based Integration pada Mata Pelajaran Ilmu Pengetahuan Alam di Sekolah Kristen ABC Sukoharjo, Jawa Tengah [The Implementation of Biblical Based Integration in Science Subject in ABC Christian School in Sukoharjo, Central Java] - Meri Fuji Siahaan; Nova Jessyca Aruan (Diligentia: Journal of Theology and Christian Education, 2022)
Teachers at a christian school ABC in Sukoharjo, Central Java are expected to implement Bible Based Integration in every lesson of the teaching. The purpose of this research was to explain the implementation of the Bible Based Integration by teachers who taught science subjects (physics, chemistry, and biology) at Christian senior high school in Sukoharjo, Central Java. A qualitative case study was conducted to explain the purpose of this research. Six science teachers were involved as subjects of this research. Research data were collected by interviewing those six teachers as well as observing their own classrooms. Interviewing students, three students from each grade (X, XI, XII) along with collecting some lesson plans of those teachers were also conducted. The data were qualitatively analyzed by coding, classifying, and labeling the data then relating each labeled data with the related literature. Data analysis showed those six teachers used three approaches to implement Bible Based Integration: relegating, referencing, and responding to the Bible. The data also revealed the teachers’ perceptions towards the Bible Based Integration.BAHASA INDONESIA ABSTRACT: Guru-guru di sekolah Kristen ABC di Sukoharjo, Jawa Tengah diharapkan dapat mengimplementasikan Integrasi Berbasis Alkitab dalam setiap pelajaran yang diajarkan. Tujuan dari penelitian ini adalah untuk menjelaskan implementasi Integrasi Berbasis Alkitab oleh guru yang mengajar mata pelajaran sains (fisika, kimia, dan biologi) di SMA Kristen di Sukoharjo, Jawa Tengah. Sebuah studi kasus kualitatif dilakukan untuk menjelaskan tujuan penelitian ini. Enam guru sains dilibatkan sebagai subjek penelitian. Data penelitian dikumpulkan dengan mewawancarai keenam guru tersebut dan juga mengamati kelas mereka sendiri. Wawancara dengan siswa, tiga siswa dari setiap kelas (X, XI, XII) serta mengumpulkan beberapa rencana pembelajaran dari guru-guru tersebut juga dilakukan. Data dianalisis secara kualitatif dengan cara mengkodekan, mengklasifikasikan, dan memberi label pada data, kemudian menghubungkan setiap data yang telah diberi label dengan literatur terkait. Analisis data menunjukkan bahwa keenam guru tersebut menggunakan tiga pendekatan dalam mengimplementasikan Integrasi Berbasis Alkitab: merelevansikan, merujuk, dan merespons Alkitab. Data juga menunjukkan persepsi para guru terhadap Integrasi Berbasis Alkitab.